PENGARUH PEMBERIAN JUS KECAMBAH KACANG HIJAU (Vigna radiata (L.) R. Wilczek)TERHADAP KUALITAS SPERMATOZOA DAN SPERMATOGENESIS MENCIT JANTAN GALUR SWISS - Yance Anas; Nur Chakim; Suharjono Suharjono (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2015)
ABSTRACT Efficacy of mung bean sprouts as natural fertility enhancer for men was not widely investigated and published. The objective of  this  study  is  to  investigate  the effect of mung bean sprout’s  juice on male Swiss mice spermatozoa quality and spermatogenesis.  An  experimental  study  performed  with randomized  matched  two-group  post  test  only  design  approach.  Thirtymale  mice  were  dividedinto fivegroups randomly, which consist of a control group (CMC25mL/kg BW/day); d-α-tocopherol group (556 IU/kg BW/day) and three mung beans sproutjuice groups (33, 66 and 132) mg/kg BW/day. Mice treated  every  dayfor  20days  orally. Micewere  sacrificed;  testis  and  epididymis  were  collected  and examined.  The  spermatozoa  quality  (count,  progressive  motility  and  normal  morphology)  and spermatogenesis observed. The  results showedthatmung bean sproutsjuice  treatment  (33, 66 and 132) mg/Kg BW/day  for 20 days did not enhance male Swiss strain mice  fertility. Spermatogenesis score, count and normal morphology spermatozoa that receive treatment with mung bean sprout juice was not significantly  different  to  the  control group  (p>0.05). Conversely; mung  bean  sprouts  juice  treatment lead to decrease male Swiss strain mice spermatozoa progressive motility (p<0,05). Keywords:   Mung  bean  sprouts  (Vigna  radiata  (L.)  R.Wilczek)  juice,  spermatozoa  quality, spermatogenesis.